Instrument for selecting and evaluating suppliers in small and medium-sized metalworking enterprises in Cartagena, Colombia (2020)
The objective of this investigation is the definition of a practical tool that helps to improve the selection process and evaluation of suppliers in small and medium-sized metalworking enterprises in Cartagena city. For this purpose, a mixed approach methodology was used where data from 30 projects in the sector were mixed, together with related literature, to identify the most relevant factors. Once the information was reviewed, the multicriteria decision method known as the analytic hierarchy process was applied, where the experience, organizational structure, project resources, technical capacity, and previous performance were used as decision-making elements for the processes related to the selection and supplier's evaluation.